2013
DOI: 10.5152/balkanmedj.2013.7785
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Tauroursodeoxycholic Acid and Glutamine on Bacterial Translocation in Obstructive Jaundiced Rats:

Abstract: Background: Bacterial Translocation is believed to be an important factor on mortality and morbidity in Obstructive Jaundiced.Aims: We investigated the probable or estimated positive effects of tauroursodeoxycholic acid, which has antibacterial and regulatory effects on intestinal flora, together with glutamine on BT in an experimental obstructive jaundiced rat model. Study Design: Animal experimentation.Methods: Forty adult, male, Sprague Dawley rats were used in this study. Animals were randomised and divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They concluded that TUDCA therapy is safe and appears to be more effective than UDCA in improving biochemical parameters [ 40 ]. Our study evaluated the effect of TUDCA in a long term cholestasis mouse model, whereas other studies often study the effect during early cholestasis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that TUDCA therapy is safe and appears to be more effective than UDCA in improving biochemical parameters [ 40 ]. Our study evaluated the effect of TUDCA in a long term cholestasis mouse model, whereas other studies often study the effect during early cholestasis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical observations and experimental studies point to the frequent occurrence of different organ complications in patients with OJ. 19 The oxidative stress known to occur as a systemic response to cholestasis could give rise to the involvement of organs other than liver, such as the lung. 3 , 20 …”
Section: Discussionmentioning
confidence: 99%